Mechanosensitive channels: feeling tension in a world under pressure - Peyronnet, Rémi; Tran, Daniel; Girault, Tiffanie; Frachisse, Jean-Marie (Frontiers in Plant Science, 2014)
Plants, like other organisms, are facing multiple mechanical constraints generated both in their tissues and by the surrounding environment. They need to sense and adapt to these forces throughout their lifetime. To do so, different mechanisms devoted to force transduction have emerged. Here we focus on fascinating proteins: the mechanosenstive (MS) channels. Mechanosensing in plants has been described for centuries but the molecular identification of MS channels occurred only recently. This review is aimed at plant biologists and plant biomechanists who want to be introduced to MS channel identity, how do they work and what they might do in planta? In this review, electrophysiological properties, regulations and functions of well characterized MS channels belonging to bacteria and animals are compared with those of plant . Common and specific properties are discussed. We deduce which tools and concepts from animal and bacterial fields could be helpful for improving our understanding of plant mechanotransduction. MS channel embedded in its plasma membrane is sandwiched between the cell wall and the cytoskeleton. The consequences of this peculiar situation are analyzed and discussed. We also stress how important it is to probe mechanical forces at cellular and subcellular levels in planta in order to reveal the intimate relationship linking the membrane with MS channel activity. Finally we will propose new tracks to help to reveal their physiological functions at tissue and plant levels.